La fanfiction dans l’enseignement des langues MoDiMEs (cas de la philologie romane) - Pudo, Dorota (Neofilolog, 2025)
Teaching writing skills at the tertiary education level, especially in the case of Less Commonly Taught (LCT) languages, is challenging, as many students have a negative attitude towards writing, particularly in its more scholarly forms. However, many young people who enjoy popular culture engage freely in extensive writing, sometimes in foreign or LCT languages, which they later publish on fanfiction websites. This article explores the potential benefits of incorporating fanfiction into a tertiary-level LCT language class from motivational, cultural, and linguistic perspectives. After reviewing existing studies in this field, an example of fanfiction practice among a group of Romance Philology students is presented, highlighting its impact on stimulating written production, fostering creativity, its playful nature, and its role in expanding vocabulary and reinforcing various grammatical structures.